Analisis filogenetik Hyposidra talaca nucleopolyhedrovirus (HytaNPV) yang diisolasi dari perkebunan teh Gunung Mas, Bogor, Jawa Barat dan virulensinya terhadap Hyposidra talaca Walker: Phylogenetic analysis of Hyposidra talaca nucleopolyhedrovirus (HytaNPV) isolated Gunung Mas tea plantation from Bogor, West Java and its virulency against Hyposidra talaca Walker - Kusumah, Yayi Munara; Kurniawati, Fitrianingrum; Kristanto, Eka Dana; Parasian, Franciskus; Christian, Michael (Perhimpunan Entomologi Indonesia, 2023)
Hyposidra talaca (Walker) is an important pest of tea plant. H. talaca can cause losses of between 40–100% in the dry season if proper control is not carried out. H. talaca has natural enemies such as predators, parasitoids, and pathogens. One of the entomopathogens is NPV. This study aims to obtain molecular characteristics through DNA polymerase sequences and determine the virulence level of NPV isolates from H. talaca. The same species from different locations can have genetic variability. Therefore, molecular characterization by polymerase chain reaction (PCR) on DNA polymerase sequences is one way to study the genetics of HytaNPV. NPV was isolated from infected H. talaca larvae collected from the field. The DNA isolates were used as templates for PCR for DNA polymerase gene amplification with an amplicon target of ±1,000 bp. A sequencing process followed the PCR provides nucleotide sequence. HytaNPV DNA polymerase sequencing results were aligned with GenBank's BLAST data to provide information on the relationship of HytaNPV to NPVs isolated from other regions. Based on molecular character analysis using DNA polymerase gene sequence, HytaNPV Bogor has a homology level of 93.9% with HytaNPV isolated from India. HytaNPV Bogor has a genetic relationship with the NPV that infects Buzura suppressaria from China and Australia. HytaNPV Bogor is similar to the NPV that infects H. talaca from India. The bioassay of HytaNPV isolate against H. talaca showed the highest LT50 value of 1.92 days was found in concentration of 1.58 x 107 POBs/ml in second instar larvae.